2000
DOI: 10.1054/bjoc.2000.1423
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transcription factor nuclear factor-κB by a mutant inhibitor-κBα attenuates resistance of human head and neck squamous cell carcinoma to TNF-α caspase-mediated cell death

Abstract: Tumour necrosis factor-α (TNF-α) is a cytokine that can induce cell death of different cancers via a cellular cascade of proteases, the caspases. However, TNF-α has been detected in tumour and serum of patients with head and neck squamous cell carcinoma (HNSCC), and tumour cell lines derived from this environment often exhibit resistance to TNF-α-induced cell death. Cell death mediated by TNF-α and caspases may be inhibited by cytoprotective genes regulated by transcription factor nuclear factor-κB (NF-κB). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 54 publications
(88 reference statements)
4
50
0
Order By: Relevance
“…Increased expression of IAP-1 (Birc2) was previously detected in metastatic SCC (4). The inhibition of IAP-1 expression with inhibition of NF-B in this study is consistent with the effect of inhibition of NF-B in sensitizing LY-2 cells to apoptosis and HNSCC to tumor necrosis factor-induced caspasemediated cell death (22). Decreased expression of ␤-catenin has been observed and associated with metastasis of human oral SCC (23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Increased expression of IAP-1 (Birc2) was previously detected in metastatic SCC (4). The inhibition of IAP-1 expression with inhibition of NF-B in this study is consistent with the effect of inhibition of NF-B in sensitizing LY-2 cells to apoptosis and HNSCC to tumor necrosis factor-induced caspasemediated cell death (22). Decreased expression of ␤-catenin has been observed and associated with metastasis of human oral SCC (23).…”
Section: Discussionsupporting
confidence: 90%
“…Constitutive activation of NF-B and NF-B-inducible genes has been detected in prostate and breast cancers, melanomas, and lymphomas (25,(37)(38)(39)(40)(41). NF-B has been implicated in promoting expression of the phenotypic changes and genes involved in inhibition of programmed and therapeutic cell death (18,22,(41)(42)(43)(44), proliferation (15), tumorigenesis (7,25,34), angiogenesis, invasiveness, and metastatic potential (9,25,38).…”
Section: Discussionmentioning
confidence: 99%
“…25 The pathway which is initially chosen may depend on the presence or absence of low constitutive NF-kB activation. Inhibition of the induction of NF-kB sensitises cells to TNF-induced toxicity, 56 and inhibition of protein synthesis appears to have a similar effect. We have shown that the protein-synthesis inhibitor, cycloheximide, sensitised TF-1 cells to TNF-induced toxicity, and this was most likely by preventing induction of protective or survival factors.…”
Section: Tnf Life/death Switching In Other Human Leukaemia Cellsmentioning
confidence: 99%
“…For example, the stepwise changes in patterns of growth and metastasis in this model have been linked to expression of angiogenesis factors, such as the C-X-C chemokine Gro-1/KC, and expression of other genes related to activation of the Nuclear Factor kappaB (NF-kB) signal pathway Loukinova et al, 2000). Identification of these factors has facilitated demonstration of the clinical and functional importance of expression of several angiogenesis factors and constitutive activation of NF-kB in human head and neck squamous cell carcinoma (HNSCC) Duffey et al, 1999).…”
Section: Introductionmentioning
confidence: 99%